Beyond 2000: Assessment of Economic Performance and an Agenda for Sustainable Growth - Josef T. Yap (Philippine Institute for Development Studies (PIDS), 1998)
Newly installed President Estrada is confronted by the same unenviable situation as his two predecessors. Former President Aquino has presided over an economy battered by the external debt crisis while President Ramos battled the aftermath of the Gulf war. The new administration, on the other hand, is facing a regional economic crisis. One section of this paper is devoted to explain the causes of the current crisis to help us understand why past policies have been ineffective to the present circumstances. However, the primary objective of the paper is to assess the performance of the economy over the period 1986-1997 and to determine how far the Philippine economy has gone. Special attention is given to the economic program of the immediate past president.
Keywords: 330; economic recovery